Tinjauan Terhadap Upaya STAIN Curup Dalam Meningkatkan Kemampuan Baca Al-Qur’an Mahasiswa - H Hardivizon; A Anrial (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2016)
This study was designed to evaluate the efforts that was made by STAIN Curup in improving the ability of students to recite the Qur’an through Tahsin al-qirâ'ah courses. The goal was to determine how effective these efforts can improve the students to recite the Qur’an. This study was an evaluation which is a systematic scientific procedures that performed to measure the results of a program, whether or not the objectives planned is suitable. By collecting, analyzing and reviewing the implemention of the programs that was conducted objectively. Then formulating and defining the policy in advance to consider the positive values and benefits of the program. The informants of this study were the Head of STAIN Curup, Tahsin al-qira'ah Lecturers, and the second or third-year students. From the result of research, it was found that the efforts made by STAIN Curup to improve students’s ability to recite al-Quran by requiring first-year students took tahsin al-qiraah courses was not very effective. It was shown from the low ability of the second and third students to recite al-Quran who have passed the course. 46.6% of students had low achievement. This happened because: (1) lack of time lecturing; (2) the lack of oversight and evaluation of the program by the Head of STAIN Curup, and (3) classification of students which were not based on the ability.